The Mediating Role of Interactivity between Perceived Usefulness, Perceived Enjoyment and Intention to Use Augmented Reality Application for Shopping - Najjia Ejaz Chaudhry; Waseem Subhani; Muhammad Azeem Naz; Muhammad Umair Nazir; Muhammad Huzaifa Ameer (Journal of Management Practices, Humanities and Social Sciences, 2023)
Augmented Reality (AR) is a technology that adds digital data created in real-time by a computer to the physical world. Offering (virtual) items opens new and fascinating ways for customers to engage with the brand and its merchandise. While the augmented Reality (AR) technology market is forecasted to experience exponential growth by 2030, numerous businesses have already endeavoured to leverage the technology to extend their operations. However, prior literature still needs to document the empirical evidence of whether AR technology adoption will positively impact or improve consumers' shopping habits based on AR technology. The study assesses the gap statistically; this work uses a survey method to determine the causal influence of many augmented reality applications on university students. A suitable sample of executive students has been chosen to investigate influences on behavioural intentions through experiments. In conclusion, the perceived usefulness and enjoyment of AR will be notably high, with a retail focus that will influence users' behavioural intentions and encourage them to make purchases through AR apps. Interactivity was highly significant, mediating the influential effect of enjoyment, perceived usefulness, and behavioural intention to use AR shopping apps and, thus, determined to be a key driver